Hubungan Pengalaman Orang Tua dengan Perilaku Belajar Anak di Rumah di Kuamang Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Zuhrina Zuhrina; Jamaris Jamaris; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
Behavior of children learning in Kuamang Subdistrict of Lembah Melintang Regency of West Pasaman still in low category. This is presumably because the experience of his parents is in the low category, so this study aims to reveal a picture of the parents experience, a picture of the behavior of children's learning in Kuamang Subdistrict of Lembah Melintang Regency of West Pasaman District, and the relationship between the two variables. This research is correlation research with teen population which amount 60 people and sample 36 people by using Area random sampling technique, where as data collection tool used is questionnaire with data analysis of percentage calculation and using Product Moment formula to see the relationship of both variables. The results showed that parents experience applied to children is in the low category, the behavior of children's learning at home is in the low category, and there is a significant relationship between the parents experience with the behavior of children's learning at home for it is suggested that parents need to improve understanding and knowledge so that the behavior of learning his son to be better again.